The Impact of Urban Shrinkage on Carbon Emission Intensity and Its Spatial Spillover Effects - Xiaochun Zhao; Xiaodan Nie (Land)
Cities are important consumers of resources, and their carbon emissions are key to realizing China’s dual-carbon goals. However, the trend of urban shrinkage has grown increasingly pronounced in recent years, and how this affects the carbon emissions of cities is a major issue that deserves to be studied. This study zeroes in on 278 Chinese cities that rank at or above the prefectural level between 2012 and 2021, employs a comprehensive analytical framework, incorporating multiple methodological approaches including entropy-based measurement, panel fixed-effects regression, mediating effect analysis, and spatial econometric modeling, to systematically investigate how urban shrinkage affects carbon emission intensity. The study’s findings indicate the following: (1) Urban contraction exacerbates the further increase in carbon emission intensity. (2) Mechanism tests show that human capital level and industrial structure advancement are the primary pathways through which urban shrinkage influences carbon intensity. (3) Urban contraction has a greater effect on increasing carbon emission intensity in central, western, and resource-dependent cities, according to the heterogeneity study. (4) Urban shrinkage lowers nearby cities’ carbon intensity through spatial spillovers.